2022 Kesiapan transformasi digital terhadap sumber daya manusia pada Organisasi Perangkat Daerah (OPD) - Widhiastono, Raymondhus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The development of cities in Indonesia is in line with the emergence of problems caused by changes in population growth and digital transformation, radical changes brought about by the use of existing resources, including today's digital technology. One of the actors and drivers of digital transformation is Human Resources who have a role and are the main factor in driving the sustainability of the implemented digital transformation. This study aims to determine the readiness of the Regional Apparatus Organization (ODP) of Semarang City with the scope of Human Resources on the concept of the Garuda Smart City Model with 3 aspects of Understanding of Transformation, Cultural Transformation, Competence and Basic Knowledge as the focus of research. By using descriptive research methods with a qualitative approach, the results of research and data processing can be concluded that the readiness of Human Resources in OPD in Semarang City is not ready and lacks understanding of understanding digital transformation, both basic and advanced, so it is necessary to use and introduce process information technology. work in the government sector that will help a sustainable and integrated digital transformation can be implemented.